2023
DOI: 10.3390/coatings13020373
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Arcs Oxidation Layer Formation on Aluminium and Coatings Tribological Properties—A Review

Abstract: This review proposes to carry out a state-of-the-art associated with micro-arc oxidation. Firstly, the different aspects of the growth mechanisms of the oxides are detailed. Then, the formation of micro-arcs and the case of soft-spark treatment are discussed. Then, the electrolytic reactions involved in the layer construction are outlined. We focused on the influence of aluminium alloys on the appearance of the coating and its characteristics before considering the electrolyte formulation. We have concentrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…The expansion of the functionality of thermally sprayed aluminum coatings after their modification using PEO processing has already been demonstrated previously [42][43][44][45][46][47][48]. For the same purpose, plasma or cold spray deposition of aluminum coatings is also used [49,50], and aluminum, steel and titanium are used as the substrates [51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The expansion of the functionality of thermally sprayed aluminum coatings after their modification using PEO processing has already been demonstrated previously [42][43][44][45][46][47][48]. For the same purpose, plasma or cold spray deposition of aluminum coatings is also used [49,50], and aluminum, steel and titanium are used as the substrates [51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 84%
“…Its hardness was 55% higher than an aluminum oxide coating formed using plasma spraying in the atmosphere (940 HV 0.1 ). X-ray diffraction analysis showed that, as a rule, the lower hardness of the PEO layer on an aluminum alloy deposited using cold spraying is due to its lower content of α-Al 2 O 3 [42]. A technological layer forms on the outer surface of the PEO layer, which has fairly high mechanical properties under wear conditions and provides good protection against corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 shows the polarization curve of the substrate and the two coated samples. The corrosion current density (I corr ) and rate (V corr ) were obtained via Tafel fitting according to the Stern-Geary equation (Equation (7), where β a is the anodic Tafel slope and β c is the cathodic slope), and Faraday's Law (Equation (8), where N is the equivalent weight and ρ is the density), respectively [7,27]. The results of the Tafel-fitted polarization curves are listed in Table 2.…”
Section: Corrosion Resistances Of the Coatingsmentioning
confidence: 99%
“…Plasma electrolytic oxidation (PEO), also called microarc oxidation (MAO), has been one of the commonly used surface treatment technologies for valve metals (aluminum, magnesium, titanium, and zirconium as well as their alloys) in recent years [7][8][9]. The ceramic coatings, which have the advantages of wear and corrosion resistance, low thermal conductivity, and a high bonding strength with the substrate, can be fabricated via PEO [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Functional protective coatings formed on aluminum alloy products through plasma electrolytic oxidation (PEO) widely broaden their applications and substantially increase the hardness and wear and corrosion resistance of alloy products [8][9][10]. Moreover, the significant advantages of this process are high productivity (the synthesis of coatings is carried out in the range of 30-40 min) and environmental friendliness, provided by the use of alkaline water-based electrolytes [11][12][13]. This process is widely applied in various industries, including the production of PEOcoated aluminum details for the oil and gas sector [14], moving mechanisms for marine applications [15], aircraft engineering [16], and the automotive industry [17], demonstrating its versatility and effectiveness across multiple fields.…”
Section: Introductionmentioning
confidence: 99%